(3JMaI GdCYdGe aj TQM Ohd GdESdGe Ydi CdajI GdSdhc aj hajGJ Gdedhcs - (3CHhGdbGSe Hf CMeO Hf Ydj GdRjGfjs
(3ChdgG (B:s
(3hfXe GddDdh hGdeQLGf ddeGRhRi GdecfGSi ai ZGjI GdHjGf s
(3BNQgG (B:s
(3aGddg jHbjc ddYdhe JfXegG fXe GdjhGbjJ ai Sdc heQLGf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B172s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B94 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs